The Eastern Slavic Chant Manuscript ‘Great Feasts’ of the National Library of Finland - Jopi Harri (The International Society for Orthodox Church Music, 2022)
The purpose of the paper is to provide a description of the 18th-century Great Feasts manuscript Sl.Ms.O-51.1 of the National Library of Finland, written in square notation: its relation to other specimens of its kind, its origins, physical shape, structure as a chant document, scribal quality and other features, palaeographical characteristics of its text and notation, and orthographical features, among other things. In addition, a dating for the manuscript is proposed, being based on a certain detail in its content. This is followed by a catalogue of the hymns included, with comments as considered necessary.
As part of the research assignment, the music of the manuscript was compared against the common chant sources, published by the Holy Synod of the Russian Orthodox Church in 1772 and later. In addition, supplementary comparisons were made against the Trinity Lavra Ms. 451 of the Russian State Library (Fond 301.I No. 451), that was found to be contemporary. It was found that even though the majority of the chants of the O-51 manuscript do not show major differences to the Synodal versions of the chants, about a third of them have extended passages of dissimilar melodic conduct. Most often this pertains to embellishments known as fity, which in the manuscript are more numerous and/or more extensive than in the Synodal chant versions. On the other hand, for the 50 hymns that have more fita passages than the Synodal sources, it was found that in this respect, the same chants in Ms. 451 were in agreement with those of the O-51, further strengthening the conclusion that this manuscript was indeed copied no later than during the first two decades of the 18th century.
While the Great Feasts manuscript of the National Library of Finland may not be a unique or excellent representative of its kind, it still is a valuable document of the tradition of Znamenny Chant from the time when the transition to staff notation had taken place relatively recently.